Effects of ripening at ambient temperature and different drying treatments on selected antioxidants and activity of Chokanan mango (Mangifera indica L.) peel and pulp - Jamali, Neda (2014)
Mango is a seasonal fruit and after the fruit is harvested at commercial maturity stage from the tree for further use in industry or market, in the forms of ripe or raw, fresh or processed it is very important to know what changes the fruit will undergo. Drying is one of the preservative methods to store the fruit for longer time before processing. Thus, the main goals of this study are to evaluate effects of ambient temperature and drying methods on antioxidant properties of mango pulp and peel. In this study, first the pulp and peel of a local variety of mango (Chokanan) was studied for its phytochemical and bioactive components such as mangiferin, gallic acid and quercetin content, total phenolic content (TPC), total antioxidant activity (TAA) and free radical scavenging activity (FRS). Subsequently, proximate analysis including protein content, moisture content, ash content, fat content and dietary fiber content of both pulp and peel of Chokanan mango were studied. The results obtained from this study shows that the peel of mango contains higher amount of mangiferin, antioxidant and phenolic compounds in comparison with mango pulp. In terms of proximate analysis pulp of this fruit tend to have more moisture content than the peel but the other parameters including dietary fiber showed higher content in peel (51%) than pulp (14.1%). Effect of ripening at ambient temperature on the antioxidant properties of pulp and peel of Chokanan mango were determined and based on the results obtained from this chapter ripening has a decreasing influence on the antioxidant activity of the Chokanan peel and flesh. Chokanan peel showed higher antioxidant properties than its pulp in all stages of ripening and as result of ripening TPC of Chokanan peel decreased 3.24% and TPC of Chokanan pulp decreased 12.46%. Due to ripening at ambient temperature FRS and TAA of Chokanan peel and pulp decreased 44.5%, 29%, 8.64% and 17.1%, respectively. Mangiferin and gallic acid content of peel (78.36% and 42.19%, respectively) and gallic acid of pulp (60.5%) tend to decrease throughout ripening but quercetin which was not detected in early stages of ripening started to increase by the end of ripening process. In a comparison between effect of three different drying techniques including vacuum oven drying, freeze drying and spray drying on the antioxidant activity of both pulp and peel of Chokanan mango it was concluded that freeze drying has the smallest decreasing influence on antioxidant action of peel and pulp of mango by keeping 76% and 54% of their TPC, respectively while spray drying has the most damaging effect on the antioxidant activity of Chokanan peel and pulp by decreasing their TPC 80% and 90%, respectively. Thus, present study identified raw mango peel as a potential source of dietary fiber and antioxidants that future researches would provide a method to convert it from a by-product to a functional food additive.